Environmental violations, refinancing risk, and the corporate bond cost in China. (18th January 2022) - Ma, Rufei; Ji, Qiang; Zhai, Pengxiang; Yang, Ruibo
Abstract: This paper examines the relationship between environmental violations and the cost of corporate bonds, and further analyzes whether refinancing constraints, the lending restrictions on penalized firms, are an important channel through which environmental violations affect the cost of corporate debt financing in China. Using the manually collected environmental violation events from 2008 to 2020, we find that the bond cost of firms violating environmental regulations increases significantly after being penalized. The finding is robust to potential sample selection bias and endogeneity problems. Furthermore, we find that the effect of environmental violations on the cost of corporate bonds is more profound in short‐term debt‐dependent firms and can be alleviated by the internal financing dependence. These results confirm that the refinancing risk arising from China's green loan policy on pollution‐intensive firms plays a key role in the relation between environmental violations and the cost of capital in the firms. In the context of the growing concerns of global society about climate change, our findings have great implications for pollution‐intensive firms, bond investors, and regulatory authorities in emerging economies to manage the increasing environmental risk.